2021
DOI: 10.1097/qad.0000000000003060
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of testing for latent tuberculosis infection in people with HIV

Abstract: The aim of this study was to estimate the cost-effectiveness of screening strategies for predicting LTBI that progresses to active tuberculosis (TB) in people with HIV.Design: We developed a decision-analytical model that constituted a decision tree covering diagnosis of LTBI and a Markov model covering progression to active TB. The model represents the lifetime experience following testing for LTBI, and discounting costs, and benefits at 3.5% per annum in line with UK standards. We undertook probabilistic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A UK study examined five TBI testing strategies for HIV-infected individual. The QuantiFERON-TB Gold In-Tube negative followed by TST strategy was the most costly and effective (ICER = £20,163/QALY), with a probability of 41% to be cost-effective at thresholds above £40,000 per QALY 49 . Another model-based cost-effectiveness study of testing for TBI also found that confirm sequential negative test (IGRA followed by TST) in non-US-born HIV patients was the preferred cost-effective strategy, with an incremental QALY (0.0008) at incremental cost USD 50 per person and ICER 63,000 USD/QALY (compared to no testing) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…A UK study examined five TBI testing strategies for HIV-infected individual. The QuantiFERON-TB Gold In-Tube negative followed by TST strategy was the most costly and effective (ICER = £20,163/QALY), with a probability of 41% to be cost-effective at thresholds above £40,000 per QALY 49 . Another model-based cost-effectiveness study of testing for TBI also found that confirm sequential negative test (IGRA followed by TST) in non-US-born HIV patients was the preferred cost-effective strategy, with an incremental QALY (0.0008) at incremental cost USD 50 per person and ICER 63,000 USD/QALY (compared to no testing) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…There are different conclusions about the predictive ability of IGRAs due to different follow-up periods, but at least patients with negative IGRAs have a low risk of ATBI in a short time [ 55 , 72 ]. Using it for predicting ATBI was reported to be cost-effective in some countries [ 73 ]. In addition, IGRAs are more convenient (one visit only) and improve screening rates for LTBI [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Latent TB infection (LTBI) is treatable through TB preventive therapy (TPT) especially when the infection occurred from index cases with drug sensitive TB, but its application has been skewed and mostly restricted to low‐burden settings until recently due to concerns over cost‐effectiveness, reinfection and resistance [6, 7]. Nevertheless, there is growing recognition of advancing the inclusion and expansion in coverage of TPT services as a key priority for TB elimination and achieving global end TB targets by interrupting the chain of TB transmission [6, 8].…”
Section: Introductionmentioning
confidence: 99%